The effect of different growing locations on the morphological characteristics and flavonoid content of clove plants (Syzygium aromaticum) - Hadiyanti, Nugraheni; Probojati, Rasyadan Taufiq; Kustiani, Edy; Sari, Sindy Permata (International Journal of Sustainable Agricultural Research, 2025)
This study investigated the effects of growing location factors on the morphological characteristics and secondary metabolite content (flavonoid) of clove. It was conducted in three locations, namely Nganjuk, Jombang, and Trenggalek, from November 2023 to February 2024. The study began with an agroclimatological analysis, including air temperature, air humidity, light intensity, and soil pH. Subsequently, the morphological characteristics of clove plants were analyzed, and clove leaf samples were collected at the three locations to test their flavonoid content. The flavonoid analysis was performed at the CNH Laboratory in Semarang, Central Java, using the UV-Vis Spectrophotometry method. The results indicated that differences in growing locations and environmental conditions affected the morphological characteristics of clove plants. The morphological traits that showed variation among the three locations included stem surface, stem color, leaf shape, leaf apex, leaf color, and leaf size. Additionally, the environmental differences influenced the flavonoid content in clove leaves, with the highest flavonoid content (0.049%) observed in leaves from Jombang. The practical implication of this study is that selecting cultivation sites for clove should consider agroclimatic conditions and soil type. The observed morphological differences among locations, despite being of the same variety, reinforce the understanding that plant adaptation to the environment results from interactions between genetic and environmental factors.